Chaco Canyon Dig Unearths Ethical Concerns - Claw, Katrina G.; Lippert, Dorothy; Bardill, Jessica; Cordova, Anna; Fox, Keolu; Yracheta, Joseph M.; Bader, Alyssa C.; Bolnick, Deborah A.; Malhi, Ripan S.; TallBear, Kimberly; Garrison, Nanibaa' A. (Human biology, 2017)
The field of paleogenomics (the study of ancient genomes) is rapidly advancing, with more robust methods of isolating ancient DNA and increasing access to next-generation DNA sequencing technology. As these studies progress, many important ethical issues have emerged that should be considered when ancient Native American remains, whom we refer to as ancestors, are used in research. We highlight a 2017 article by Kennett et al., “Archaeogenomic evidence reveals prehistoric matrilineal dynasty,” that brings to light several ethical issues that should be addressed in paleogenomics research. The study helps elucidate the matrilineal relationships in ancient Chacoan society through ancient DNA analysis. However, we, as Indigenous researchers and allies, raise ethical concerns with the study's scientific conclusions that can be problematic for Native American communities: (1) the lack of tribal consultation, (2) the use of culturally insensitive descriptions, and (3) the potential impact on marginalized groups. Further, we explore the limitations of the Native American Graves Protection and Repatriation Act, which addresses repatriation but not research, because clear ethical guidelines have not been established for research involving Native American ancestors, especially those deemed “culturally unaffiliated.” Multiple studies of “culturally unaffiliated” remains have been initiated recently, so it is imperative that researchers consider the ethical ramifications of paleogenomics research. Past research indiscretions have created a history of mistrust and exploitation in many Native American communities. To promote ethical engagement of Native American communities in research, we therefore suggest careful attention to ethical considerations, strong tribal consultation requirements, and greater collaborations among museums, federal agencies, researchers, scientific journals, and granting agencies.